Energy Storage Management Control For Nine-Level Inverter Based On Super-Capacitors - Mohammed Rasheed; Omar, Rosli; Sulaiman, Marizan; Halim, Wahidah (Medwell Publications, 2019)
In this study, modified multilevel inverters based on Newton Raphson (NR) and Particle Swarm Optimization (PSO) techniques were presented. A NR and PSO techniques were presented for Selective Harmonics Elimination (SHE) solution in a modified Cascaded H Bridge Multilevel Inverter (CHB-MLI). The Selective Harmonic Elimination Pulse-Width Modulation (SHE-PWM) is a powerful technique for harmonic minimization in multilevel inverter. The proposed design was used to charge the energy storage such as battery, super capacitor. NR and PSO techniques were used to determine the switching angles by solving the non-linear equation’s analysis of the output voltage waveform of the modified CHB-MLI in order to control the fundamental component. The proposed techniques based on NR and PSO techniques are capable to minimize the Total Harmonic Distortion (THD) of output voltage of the modified CHB-MLI within allowable limits. A comparison has been made between NR and PSO techniques related to optimization in order minimize harmonic distortion. The main aims of this study cover design, modeling, construction and testing of a laboratory the modified topology of the CHB-MLI for a single-phase prototype for nine levels. The experimental results of the prototype were also, illustrated. The controllers based on NR and PSO were applied to the modified multilevel inverter. The Digital Signal Processing (DSP) TMS320F2812 is used to implement these modified inverters control schemes using NR and PSO method. The proposed controller was then coded into a DSP TMS320F2812 board. The inverter offers much less THD using PSO scheme compared with the NR scheme.